Bacterial Outer Membrane Vesicles and Immune Modulation of the Host - Lily A. Charpentier; Emily F. Dolben; Matthew R. Hendricks; Deborah A. Hogan; Jennifer M. Bomberger; Bruce A. Stanton (Membranes, 2023)
This article reviews the role of outer membrane vesicles (OMVs) in mediating the interaction between Gram-negative bacteria and their human hosts. OMVs are produced by a diverse range of Gram-negative bacteria during infection and play a critical role in facilitating host–pathogen interactions without requiring direct cell-to-cell contact. This article describes the mechanisms by which OMVs are formed and subsequently interact with host cells, leading to the transport of microbial protein virulence factors and short interfering RNAs (sRNA) to their host targets, exerting their immunomodulatory effects by targeting specific host signaling pathways. Specifically, this review highlights mechanisms by which OMVs facilitate chronic infection through epigenetic modification of the host immune response. Finally, this review identifies critical knowledge gaps in the field and offers potential avenues for future OMV research, specifically regarding rigor and reproducibility in OMV isolation and characterization methods.